2001
DOI: 10.1063/1.1358357
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of magnetite in the exhausted material from a diesel engine

Abstract: Magnetite was detected in the particulate matter collected from diesel engine exhaust using a total exhaust dilution tunnel. This discovery is very important in determining the health effects of exposure to magnetite or its interaction with static magnetic fields or low-frequency electromagnetic fields. Magnetite is the best absorber of microwave radiation of any biological material in the 0.5–10 GHz frequency range through the process of electromagnetic resonance. This includes the frequencies that are normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…The production of iron oxides from the combustion of diesel fuel was also reported by Kasper et al (1999), which found that carbonaceous matter preferentially condenses at the surface of the iron oxide nuclei. Abdul-Razzaq and Gautam (2001) reported magnetite in particulate matter collected from diesel engine exhaust; and recently, Kim et al (2007) -on two magnetic extracts -also found iron oxides from diesel vehicle emissions and from the abrasion of brake lining surfaces. The presence of these magnetic carriers is not only important because of their relationship with heavy metals but also because of their adverse influence on human health.…”
Section: 1 2 R O a D S I D E S O I L Smentioning
confidence: 96%
See 1 more Smart Citation
“…The production of iron oxides from the combustion of diesel fuel was also reported by Kasper et al (1999), which found that carbonaceous matter preferentially condenses at the surface of the iron oxide nuclei. Abdul-Razzaq and Gautam (2001) reported magnetite in particulate matter collected from diesel engine exhaust; and recently, Kim et al (2007) -on two magnetic extracts -also found iron oxides from diesel vehicle emissions and from the abrasion of brake lining surfaces. The presence of these magnetic carriers is not only important because of their relationship with heavy metals but also because of their adverse influence on human health.…”
Section: 1 2 R O a D S I D E S O I L Smentioning
confidence: 96%
“…Although there are magnetic mapping studies of traffic-related areas, most of them focussed on the influence of pollutants on nearby soils, vegetation and dust particles. There is a scarcity of rockmagnetic studies of primary sources, such as soot and material from exhaust pipes (AbdulRazzaq and Gautam, 2001;Lu et al, 2005), as well as from the brake lining system of vehicles. This information can be useful for future investigation on identifying different contamination sources from vehicles and their influence.…”
Section: Introductionmentioning
confidence: 99%
“…Frictional heating, e.g., of brake pads, can also produce high-temperature magnetite nanoparticles (21). Magnetite can arise from combustion of many types of organic matter, depending on heating temperature and atmosphere, and source Fe content (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…The soft behaviour of hysteresis loops (Table 3) as well as the low frequency dependence of magnetic susceptibility is typical features that distinguish anthropogenic ferrimagnetics from natural ferrimagnetic minerals that occur often as SP grains. Magnetite in the combustionderived component of vehicle exhaust materials has been identified (Abdul-Razzaq and Gautam 2001;Simao et al 2006). Vehicles have been suggested to generally produce non-spherical magnetite particles via exhaust emissions and the abrasion or corrosion of the vehicle engine and body work (Matzka and Maher 1999).…”
Section: Magnetic Carriers Derived Traffic Activities In Soilsmentioning
confidence: 99%